Gastric digestion of cow milk, almond milk and oat milk in rats. Issue 21 (18th October 2022) - Wang, Xin; Wolber, Frances M.; Ye, Aiqian; Stroebinger, Natascha; Hamlin, Aimee; Zhu, Peter; Montoya, Carlos A.; Singh, Harjinder
Abstract : In this study, gastric digestion of isocaloric and iso-macronutrient cow milk, almond milk and oat milk were compared in rats euthanized at different post-feeding times. Abstract : In this study, gastric digestion of isocaloric and iso-macronutrient cow milk, almond milk and oat milk were compared in rats euthanized at different post-feeding times. The cow milk separated into a curd phase and a liquid phase in the rat stomach. This coagulation of the cow milk led to higher ( P < 0.05) protein and lipid retention in the stomach compared with almond milk and oat milk. Almond milk oil bodies aggregated, creamed and rapidly layered in the stomach. This induced a faster ( P < 0.05) gastric emptying of proteins ( T 1/2 = 36 min) compared with cow milk ( T 1/2 = 89 min) and oat milk ( T 1/2 = 55 min), and a slower gastric emptying of almond lipids than of almond proteins. In contrast, no significant physical change during the digestion of oat milk was found, with both the proteins and the lipids being steadily emptied from the stomach. This in vivo study provides information on the gastric digestion and emptying (and thereby nutritional characteristics) of plant-based milks compared with animal-based milks, that will be useful for the design of novel plant-based drinks.